Chronic Hepatitis C Virus Infection Modulates the Transcriptional Profiles of CD4+ T Cells - Michal Holub; Alžběta Stráníková; Ondřej Beran; Simona Arientová; Oldřich Bartoš; Kateřina Kondelková; Stanislav Plíšek; Pavel Chalupa (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Chronic hepatitis C (CHC) is associated with altered cell-mediated immune response. Objective. The aim of the study was to characterize functional alterations in CD4+ T cell subsets and myeloid-derived suppressor cells (MDSCs) during chronic hepatitis C virus (HCV) infection. Methodology. The expression levels of the lineage-defining transcriptional factors (TFs) T-bet, Gata3, Rorγt, and Foxp3 in circulating CD4+ T cells and percentages of MDSCs in peripheral blood were evaluated in 33 patients with CHC, 31 persons, who had spontaneously cleared the HCV infection, and 30 healthy subjects. Analysis. The CD4+ T cells TFs T-bet (T-box expressed in T cells), Foxp3 (Forkhead box P3 transcription factor), Gata3 (Gata-binding protein 3), and Rorγt (retinoic-acid-related orphan receptor gamma) and activation of CD8+ T cells, as well as percentages of MDSCs, were measured by multicolor flow cytometry after intracellular and surface staining of peripheral blood mononuclear cells with fluorescent monoclonal antibodies. Result. The patients with CHC had significantly lower percentages of CD4+ T cells expressing Rorγt and Gata3 and higher percentages of Foxp3-expressing CD4+ T cells than healthy controls and persons who spontaneously cleared HCV infection. The ratios of T-bet+/Gata3+ and Foxp3+/Rorγt+ CD4+ T cells were the highest in the patients with CHC. In the patients with CHC, the percentages of Gata3+ and Rorγt+ CD4+ T cells and the percentages of T-bet+ CD4+ T cells and CD38+/HLA-DR+ CD8+ T cells demonstrated significant positive correlations. In addition, the percentage of CD38+/HLA-DR+ CD8+ T cells correlated negatively with the percentage of MDSCs. Conclusion. Chronic HCV infection is associated with downregulation of TFs Gata3 and Rorγt polarizing CD4+ T cells into Th2 and Th17 phenotypes together with upregulation of Foxp3 responsible for induction of regulatory T cells suppressing immune response.